68 Adjuvant chemotherapy in WHO Grade 2 Astrocytoma: Retrospective Analysis at NNUH to Inform a Multicentre Comparative Study - Clare Hannon; Rebecca Brooks; Pinelopi Gkogkou; Andrew Ho (Neuro-Oncology, 2026)
Abstract Background The optimal adjuvant chemotherapy for WHO grade 2 astrocytoma remains uncertain. UK NICE guidance recommends radiotherapy followed by PCV chemotherapy in higher-risk patients; however, temozolomide (TMZ) is sometimes used due to efficacy data in grade 3 astrocytoma as well as its favourable tolerability and ease of administration. No randomised trials directly compare PCV and TMZ in this population, and real-world data on toxicity, treatment adherence, and outcomes remain limited. Retrospective analyses can provide valuable insight into contemporary practice, feasibility, and comparative effectiveness. Method In a retrospective review of patients with WHO grade 2 astrocytoma treated at Norfolk and Norwich University Hospital from 2016 we identified 21 patients who met molecular criteria for grade 2 astrocytoma and received adjuvant chemotherapy. All patients received PCV. Data for patients prior to WHO 2016 criteria is limited by incomplete molecular data. Building on this experience, we propose a UK multicentre retrospective cohort study comparing adjuvant PCV versus TMZ in adults (≥18 years) with histologically confirmed, IDH-mutant, 1p/19q non-codeleted grade 2 astrocytoma treated with surgery and radiotherapy followed by adjuvant chemotherapy. The primary endpoint is progression-free survival (PFS). Secondary endpoints include overall survival (OS), treatment-related toxicity, and treatment completion rates. Given the prolonged natural history of this disease, the immediate aim is to generate comparative data on treatment patterns, PFS, and toxicity, providing a foundation for future OS analyses. Conclusions The proposed multicentre retrospective study will provide the largest UK comparative analysis of adjuvant PCV versus TMZ in WHO grade 2 astrocytoma, integrating survival and toxicity outcomes to inform clinical decision-making and future prospective or registry-based research. If you would like to participate in the multicentre study or receive further information, please contact clare.hannon@nnuh.nhs.uk